An Interactive Process for Delivering Pharmacologic Interventions for Migraine Headache to First-Year Medical Students - Jennifer Cleveland; Renée J. LeClair (Association of American Medical Colleges, 2020)
Introduction This interactive didactic session is designed for first-year medical students to explore the common clinical symptom of headache and its various management strategies. The session provides an opportunity to cover a variety of drugs, mechanisms of action, drug-drug interactions, and routes of administration in a single 50-minute time frame. Methods Using a modified case-based approach, we designed an interactive session for 41 first-year medical students. Students prepared for the session using basic learning objectives and a table of drugs that treat headache pain. In class, we distributed a patient scenario and a series of discussion questions to explore headache management. We assessed student performance using questions purchased from the National Board of Medical Examiners and student perceptions using both qualitative and quantitative data collected from faculty and end-of-block evaluations. Results Student performance on purchased questions related to content was significantly increased when compared to the national average (n = 5; 90.6% ± 6.0% vs. 82.6% ± 8.5%; p = .0052). Student perceptions of the overall quality of the faculty, content presentation, and material were positive (4.4 out of 5.0). Two themes emerged in the end-of-block evaluations: Students commented positively on the prereading materials, and students commented on the need to address underlying physiology associated with the discussed pharmacology. Discussion This flexible activity can be delivered in a short time (50 minutes) by a single faculty member in a variety of curricular structures. Our data demonstrate strong student performance and suggest that incorporating additional content would enhance delivery.